Trends in immune cell profiles of osteomyelitis: a clinical study supported by Mendelian randomization analysis - Liu, Zemin; Jin, Guochao; Zhi, Yanming; Ge, Shengxian; Wang, Dong; Li, Juan; Li, Yan; Zhang, Yonghong (Frontiers in Medicine, 2025)
BackgroundOsteomyelitis, a persistent inflammatory bone disease, is only partially responsive to conventional antibiotics and surgery. Some patients experience poor outcomes and relapse. Recently, immunotherapy has emerged as a promising treatment strategy. This study combined clinical research with Mendelian randomization analysis to explore the interaction and relationship between immune cells and osteomyelitis, aiming to offer novel therapeutic insights.MethodsWe retrospectively analyzed blood test data from patients admitted between July 1, 2023, and December 31, 2024, including those undergoing internal fixator removal and those with osteomyelitis. Based on the bacterial culture results, patients with osteomyelitis were categorized into four subgroups: Gram-positive, Gram-negative, mixed infections, and culture-negative. The impact of bacterial infections on immune cells was assessed, and two-sample Mendelian randomization was applied to evaluate the bidirectional causality between immune cells and osteomyelitis. Causal effects were primarily estimated using inverse-variance weighted and weighted-median methods, with F-statistic calculations and sensitivity analyses conducted to bolster the credibility of the results.ResultsCompared to the internal fixator removal group, patients with osteomyelitis exhibited significantly reduced neutrophils but elevated lymphocytes, eosinophils, and basophils. Subgroup analysis revealed significantly increased lymphocyte counts and decreased neutrophil counts across all subgroups, except for the mixed infection group. Two-sample Mendelian randomization indicated a causal link between circulating lymphocytes and osteomyelitis risk [odds ratio (OR): 1.203; 95% confidence interval (CI): 1.064–1.362; p = 0.003], supported by weighted median analysis (OR: 1.273; 95% CI: 1.047–1.549; p = 0.016). Sensitivity analyses confirmed the robustness and reliability of the results with no significant pleiotropy or heterogeneity.ConclusionOsteomyelitis was associated with significant alterations in peripheral immune cell counts, particularly lymphocyte counts, which showed a strong positive correlation with the disease risk. These findings pave the way for future immunotherapeutic approaches for the treatment of osteomyelitis.